The Impact of School Preventive Measures on the Aggression of Adolescents from Single-Parent Families (Journal of Educational Sciences, 2025)
This article provides a comprehensive analysis of the impact of school preventive measures on the aggression of adolescents from single-parent families. Adolescent aggressive behavior, particularly among students from incomplete families, has been increasingly studied in recent years. The relationship between adolescent behavior patterns is complex and multifaceted. In our study, the causes and specific features of aggression among adolescents from single-parent families were examined, with a focus on the effectiveness of school-based preventive measures. A survey was conducted to assess key indicators such as emotional instability, verbal and indirect aggression, and susceptibility to bullying. The study involved 75 teenagers from a school in Shymkent.  The results demonstrated that most adolescents from single-parent families have difficulties in controlling their emotions, a significant proportion frequently exhibit anger, and many report experiencing bullying. In comparison, students from intact families showed much lower rates of these indicators. Theoretical grounding for the study drew on the works of national and international scholars. Particular emphasis was placed on the importance of positive school climate, psychological training, and mediation in reducing aggression. In addition, the influence of socioeconomic and cultural factors was discussed. The findings confirmed that collaborative efforts between schools, parents, and psychologists facilitate social adaptation and help reduce aggression among adolescents.            Keywords: single-parent family, adolescent, aggression, bullying, prevention, school climate.